2020
DOI: 10.3390/jzbg1010003
|View full text |Cite
|
Sign up to set email alerts
|

Social, Reproductive and Contextual Influences on Fecal Glucocorticoid Metabolites in Captive Yangtze Finless Porpoises (Neophocaena asiaeorientalis asiaeorientalis) and Bottlenose Dolphins (Tursiops truncatus)

Abstract: Although the use of fecal glucocorticoid metabolite (FGCM) measurements as non-invasive biomarkers for the stress response in mammals has increased, few studies have been conducted in odontocetes. We investigated if animal sex, age, pregnancy or contextual variations (season, sampling time, enrichment, social separation and presence of visitors) influenced the FGCM concentrations in presumably healthy, captive and endangered Yangtze finless porpoises (YFPs, N = 4) and bottlenose dolphins (BDs, N = 3). For YFPs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 80 publications
0
3
1
Order By: Relevance
“…While age was a significant predictor of cortisol for Tursiops truncatus in the current study, age has not been a significant predictor in previous reports [ 16 , 34 ]. Month was a significant predictor of cortisol for Tursiops aduncus in the current study, similar to seasonal variations observed in previous work [ 31 ].…”
Section: Discussioncontrasting
confidence: 80%
“…While age was a significant predictor of cortisol for Tursiops truncatus in the current study, age has not been a significant predictor in previous reports [ 16 , 34 ]. Month was a significant predictor of cortisol for Tursiops aduncus in the current study, similar to seasonal variations observed in previous work [ 31 ].…”
Section: Discussioncontrasting
confidence: 80%
“…Tetrahydrocortisone is commonly measured in urine as a marker of cortisol production and metabolism [ 69 ]. In cetaceans, elevated concentrations of fecal glucocorticoids during pregnancy have been observed in the North Atlantic right whale ( Eubalaena glacialis ) [ 70 ], blue whale ( Balaenoptera musculus ) [ 38 ], humpback whales ( Megaptera novaeangliae ) [ 71 ], and YFPs [ 72 ]. Furthermore, long-term continuous monitoring by Steinman et al.…”
Section: Discussionmentioning
confidence: 99%
“…However, differences in maternal style also may have moderated the strength of other social relationships. Positive social relationships can enhance the welfare of dolphins under professional care [50,63]. Social behaviors, such as synchronous swimming, are associated with positive affective states [64].…”
Section: Discussionmentioning
confidence: 99%